Pengaruh Current Ratio, Debt to Equity Ratio dan Debt to Asset Ratio terhadap Return on Equity pada Perusahaan Konsumen Nonprimer yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019 - Qhadila Qhadila; Eka Purnama Sari (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
This research aims: (1) to determine the influence of the Current Ratio on Return On Equity in Non-Primary Consumer Companies listed on the Indonesia Stock Exchange for the 2016-2019 Period, (2) To determine the influence of the Debt to Equity Ratio on Return On Equity in Non-Primary Consumer Companies Primary listed on the Indonesian Stock Exchange for the 2016-2019 Period, (3) To determine the influence of the Debt to Asset Ratio on Return On Equity in Non-Primary Consumer Companies listed on the Indonesian Stock Exchange for the 2016-2019 Period, (4) To determine the influence of the Current Ratio , Debt to Equity Ratio and Debt to Asset Ratio on Return on Equity in Non-Primary Consumer Companies listed on the Indonesian Stock Exchange for the 2016-2019 Period. The method in this research uses a quantitative approach, the number of samples in this research is 40 companies. The data collection technique in this research uses data obtained from financial reports of Non-Primary Consumer companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The data analysis technique uses multiple linear regression tests and descriptive statistics. Data processing in this research used SPSS 29.0 for Windows. Based on research, it shows that the Current Ratio has a positive and significant effect on Return On Equity with the Asymp value. Sig. (2-tailed) of 0.007, the Debt to Equity Ratio has no positive and insignificant effect on Return On Equity with the Asymp value. Sig. (2-tailed) of 0.881, the Debt to Asset Ratio has no negative and insignificant effect on Return On Equity with the Asymp value. Sig. (2-tailed) of 0.608, and simultaneously the Current Ratio, Debt to Equity Ratio and Debt to Asset Ratio together have a positive and significant effect on Return On Equity with the Asymp value. Sig. (2-tailed) of 0.019.